Determine Role of IL-5 and Eosinophils in Chronic Bronchial Asthma - Mustafa Hamoodi Jabbar; Nasreen Rahman Mohammed; Fadhaa Jaber Shinjar; Heba Suhail kadhem; Zainab Abd Ali Salman (Peerian Journals Publishing, 2023)
Asthma is a chronic inflammatory disease, primarily resulting from interactions between genetic and environmental factors, in which immunological mediators and cells play a key role. This study aimed to determine role IL-5 and eosinophilia in chronic asthma
Keywords: Asthma; Eosinophils; ELISA